Jawabanmu

Jawaban paling cerdas!
2014-04-26T18:26:38+07:00
lim    x^2-3x-4    =
x-> 4  2-√x

lim    x^2-3x-4  × 2+√x
   x-> 4  2-√x         2+√x
= lim    (x-4) (x+1) (2+√x)
   x-> 4        4-x
= lim      (x+1) (2+√x)
   x-> 4        -1
= (4+1) (2+√4)
          -1
= -(5 . 4)
= -20

Semoga membantu ^_^

1 5 1
2014-04-26T19:34:31+07:00
Lim  x² - 3x - 4  = Lim  ( x² - 3x - 4)( 2 + √x)
x⇒4  2 - √x          x⇒4     (2 - √x)(2 + √x)
                       =  Lim  ( x - 4)(x + 1)( 2 + √x)
                           x⇒4   (2 - √x)(2 + √x)
                       =  Lim  -( 4 - x)(x + 1)( 2 + √x)
                           x⇒4         (4 - x)
                       = lim -(x + 1)( 2 + √x)
                          x⇒4
                       = -(4 + 1)(2 + √4)
                       = - 5(2 + 2)
                       = -20
1 5 1